Martin Munro. Writing on the Fault Line: Haitian Literature and the Earthquake of 2010. Liverpool: Liverpool University Press, 2014. - Linda Alcott (Studies in 20th & 21st Century Literature, 2016)
Review of Martin Munro. Writing on the Fault Line: Haitian Literature and the Earthquake of 2010. Liverpool: Liverpool University Press, 2014.
Keywords: Haiti; Haitian; earthquake; literature